Inferences About Avatars: Sexism, Appropriateness, Anthropomorphism, and the Objectification of Female Virtual Representations. Issue 5 (8th June 2015) - Nowak, Kristine L.; Fox, Jesse; Ranjit, Yerina S.
Abstract: This study integrated the computers as social actors (CASA) framework with objectification theory to predict that traits, such as sexism, influence perceptions of virtual representations as well as attributions of the source and message. Participants ( N = 397) received a message about dating or job interviews presented by a virtual woman in either context-appropriate or context-inappropriate dress. Causal modeling techniques revealed that participants higher on sexism rated the representations as less human (i.e., less anthropomorphic) and less credible. Further, perceived appropriateness of clothing and anthropomorphism influenced perceptions of source trust and message clarity. Implications for understanding the role of trait variables such as sexism on perceptions of virtual representations are discussed.